Unexpected Normal Colloid Osmotic Pressure in Clinical States with Low Serum Albumin - Michelis, Regina; Sela, Shifra; Zeitun, Teuta; Geron, Ronit; Kristal, Batya (PloS one, 2016)
In clinical states associated with systemic oxidative stress (OS) and inflammation such as chronic kidney disease (CKD), oxidative modifications of serum albumin impair its quantification, resulting in apparent hypoalbuminemia. As the maintenance of oncotic pressure/colloid osmotic pressure (COP) is a major function of albumin, this study examined the impact of albumin oxidation on COP, both in-vivo and in-vitro. Patients with proteinuria and patients on chronic hemodialysis (HD) with systemic inflammation and OS were enrolled. Blood samples were collected from 134 subjects: 32 healthy controls (HC), proteinuric patients with high (n = 17) and low (n = 31) systemic inflammation and from 54 patients on chronic hemodialysis (HD) with the highest levels of OS and inflammation. In-vitro oxidized albumin showed significantly higher COP values than non-oxidized albumin at identical albumin levels. In vivo, in hypoalbuminemic HD patients with the highest OS and inflammation, COP values were also higher than expected for the low albumin levels. The contribution to COP by other prevalent plasma proteins, such as fibrinogen and immunoglobulins was negligible. We imply that the calculation of COP based on albumin levels should be revisited in face of OS and inflammation. Hence, in hypoalbuminemic proteinuric patients with systemic OS and inflammation the assumption of low COP should be verified by its measurements.